(untitled) (UNED Research Journal, 2020)
Introduction: Snakes suffer persecution by humans for misperception, misinformation, and fear. In addition, snakes are threatened by habitat decline, which leads them to seek new territories, favoring human-snake encounters. In Costa Rica these threats also exist in the inhabitants of the city, even in those with a high academic level. To favor the conservation of snakes, it is necessary to implement environmental education strategies aimed at a specific target audience. One possible tool is the creation and dissemination of educational videos, which increase knowledge and improve decision-making for their conservation. Objective: Evaluate the effectiveness of an educational video as a tool to change the perception and knowledge about snakes in adults of high educational level in Costa Rica. Methods: We worked with 340 officials from the UNED headquarters, to whom we had applied an initial diagnosis in 2019. We separated the same participants into two groups: 240 officials received an educational video on snakes from the Greater Metropolitan Area (GAM) that we generated for them and 100 officials received a journalistic video as a control group. Finally, we evaluate their responses in a comparative way with respect to the previous diagnosis. Results: After observing the respective video, 75% of the officials maintain their perception of snakes and 68% would act in the same way in case of an encounter. However, 51,5% showed improvement in their general knowledge about snakes, showing dependence on the video observed. Conclusions: The educational video improved the general knowledge about snakes, but the environmental education effort has to face a high percentage of disinterest on the part of the population, which is a challenge for the conservation of snakes.